COMMENT ON THE RESULTS OF AMNIOCENTESIS IN CASES OF FETUS WITH INCREASED NUCHAL TRANSLUCENCY AT NGHE AN OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objectives: Comment on the results of amniocentesis in cases of fetus with increased nuchaltranslucency at Nghe An Obstetrics and Pediatrics Hospital.Subjects and research methods: Prospective descriptive study of pregnant women whoreceived ultrasound between 11 weeks and 13 weeks and 6 days of gestation with nuchaltranslucency measured and fetuses with increased nuchal translucency with genetic testing resultsfrom amniotic fluid at Nghe An Obstetrics and Pediatrics Hospital from August 2021 to August2022.Results: General characteristics: The average age of pregnant women is 30.1 ± 5.5. The groupfrom over 35 years old accounted for 20.3%. The rate of history of birth defects accounted for2.0%. Comment on the results of amniocentesis in cases of fetus with increased light at the nape ofthe neck: 61.2% of cases were indicated to have amniocentesis to make fetal chromosomalchromosomal chromosomal abnormalities due to increased light at the nape of the neck alone. Theremaining 38.8% were associated with other abnormalities. Amniocentesis at the ideal time from16 to 20 weeks accounts for 100%. The rate of chromosomal abnormalities is 2.3%.Conclusions: The rate of chromosomal abnormalities is 2.3%, of which the most commonchromosomal abnormalities are trisomy 21 and sex chromosome abnormalities.
Keywords: Nuchal translucency, fetus.